Systemic lupus erythematosus in pregnancy - intricate, but wieldy - Mohindra, Ritin; Marwah, Sheeba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Systemic Lupus Erythematosus (SLE) predominantly afflicts young women in reproductive age. In this context, it is only rational that pregnancy and its outcome becomes an imperative concern for the lupus patients and their health care providers. Queries regarding the risk of disease flares during pregnancy, chance of fetal loss, and the safety of various drugs are often raised. However the present day availability of effective treatment regimens has meant that many patients achieve protracted remissions and better disease control. Indeed, a high proportion of lupus patients, with professional care, can thus look forward to a successful pregnancy.1 This article reviews the contemporary concepts regarding SLE and pregnancy, especially regarding the fertility rate, optimal timing of conception, risk of disease flares during lupus pregnancy, pregnancy course, fetal outcome, safety of various drugs used for disease control during pregnancy and lactation, and contraceptive advice.